The Effect of Storytelling on Ability to Control Violence Behavior in Early Childhood - Rana Skharninda; Wahyu Endang Setyowati (Universitas Airlangga, 2020)
Introduction:Storytelling is a narrative activity that is close to children. This activity can convey the contents of stories, feelings or ideas without making the children feel like being patronized. Narrators can also convey or teach about the behavior that children should do. Early children often do aggressive or violent actions. Based on the condition, storytelling becomes a way to teach children about good behavior. The purpose of the study was to determine the effect of storytelling on the ability to control violent behavior in early childhood at one of Kindergarten in Semarang.Methods: This research is a quantitative research. Sampling technique used total sampling with 24 students as respondents. The data obtained were processed statistically using the marginal homogeneity test. Using marginal homogeneity test, it was obtained p value of 0,000 (<0.05).Results: It can be concluded that there is a storytelling effect on the ability to control violent behavior in early childhood.Conclusion: There is an effect of storytelling on the ability to control violent behavior in early childhood among students of one of Islamic kindergarten in Semarang. For institutions, the storytelling method can be used as daily learning because learning is not only about academics but also attitudes.